Physical Extraction and Fast Protein Liquid Chromatography for Purifying Flagella Filament From Uropathogenic Escherichia coli for Immune Assay - Acharya, Dhruba; Sullivan, Matthew J.; Duell, Benjamin L.; Eveno, Tanguy; Schembri, Mark A.; Ulett, Glen C. (Frontiers in Cellular and Infection Microbiology, 2019)
Flagella are expressed on the surface of a wide range of bacteria, conferring motility and contributing to virulence and innate immune stimulation. Host-pathogen interaction studies of the roles of flagella in infection, including due to uropathogenic Escherichia coli (UPEC), have used various methods to purify and examine the biology of the major flagella subunit protein, FliC. These studies have offered insight into the ways in which flagella proteins interact with host cells. However, previous methods used to extract and purify FliC, such as mechanical shearing, ultracentrifugation, heterologous expression in laboratory E. coli strains, and precipitation-inducing chemical treatments have various limitations; as a result, there are few observations based on highly purified, non-denatured FliC in the literature. This is especially relevant to host-pathogen interaction studies such as immune assays that are designed to parallel, as closely as possible, naturally-occurring interactions between host cells and flagella. In this study, we sought to establish a new, carefully optimized method to extract and purify non-denatured, native FliC from the reference UPEC strain CFT073 to be suitable for immune assays. To achieve purification of FliC to homogeneity, we used a mutant CFT073 strain containing deletions in four major chaperone-usher fimbriae operons (type 1, F1C and two P fimbrial gene clusters; CFT073delta4). A sequential flagella extraction method based on mechanical shearing, ultracentrifugation, size exclusion chromatography, protein concentration and endotoxin removal was applied to CFT073delta4. Protein purity and integrity was assessed using SDS-PAGE, Western blots with anti-flagellin antisera, and native-PAGE. We also generated a fliC-deficient strain, CFT073delta4deltafliC, to enable the concurrent preparation of a suitable carrier control to be applied in downstream assays. Innate immune stimulation was examined by exposing J774A.1 macrophages to 0.05-1 microgram of purified FliC for 5 h; the supernatants were analyzed for cytokines known to be induced by flagella, including TNF-alpha, IL-6 and IL-12; the results were assessed in the context of prior literature. Macrophage responses to purified FliC encompassed significant levels of several cytokines consistent with prior literature reports. The purification method described here establishes a new approach to examine highly purified FliC in the context of host-pathogen interaction model systems.